-3(8x+2)+3x=7-8x

Simple and best practice solution for -3(8x+2)+3x=7-8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(8x+2)+3x=7-8x equation:


-3(8x+2)+3x=7-8x

We simplify the equation to the form, which is simple to understand
-3(8x+2)+3x=7-8x

Reorder the terms in parentheses
+(-24x-6)+3x=7-8x

Remove unnecessary parentheses
-24x-6+3x=+7-8x

We move all terms containing x to the left and all other terms to the right.
-24x+3x+8x=+7+6

We simplify left and right side of the equation.
-13x=+13

We divide both sides of the equation by -13 to get x.
x=-1

See similar equations:

| (3x-21)(x+1)=0 | | -60z^5+55z^4+25z^3=0 | | 4x-25=3x+18 | | -20=-2(v+3) | | (3x-3)(x+7)=0 | | 60z^5+55z^4+25z^3=0 | | p+0.13=53.11 | | 16-(2.1+4.5)0.2= | | -6(v-6)=78 | | u=18v | | 3n-p=6m | | t^2+t-20=0 | | p-0.13=53.11 | | 6*6=c | | 5d+2d+4d+1d=72 | | 20y^2+72y-32=0 | | 40=4(x+7) | | h/7=31 | | y=2x^2+8x+16 | | h/7=7 | | -4(1+2x)=44 | | 8m^2+14m+3=0 | | -36=-3-3(x+5) | | (6-5t)2= | | 6x+24=-2x | | 8.4o-6.8=-4.2+6.3o | | k/5=3 | | 50=6(k+8)-5k | | (x-7)-(6x+6)= | | 4x+3y=-40 | | 5x^2+3x-14=0 | | 4s^2+33s+54=0 |

Equations solver categories